Modelo de análisis espacial multicriterio para la implementación de parques solares mediante Arcgis - caso de aplicación: Empresa Eléctrica Ambato regional centro norte S.A. - Chamba Cumbicos, Jimmy Dennis (2021)
This paper shows a multi-criteria spatial analysis model for the implementation of solar parks using ArcGIS tool; applied to Empresa Eléctrica Ambato Regional Centro Norte S.A. (EEASA) with the purpose of forecasting the optimal location of PV systems, in turn allowing the proper long-term planning (2030) in the distribution system. The development of this project was carried out in three main stages. The first comprises a suitability analysis based on multi-criteria decision making methods (MCDM); environmental, location, orographic, geological and climatic criteria are used, which are evaluated in a hierarchical analytical process (AHP), resulting in a suitability map. In the second stage, the density map is coupled, in previous support of a research study carried out, which is based on the methodology of electricity demand forecasting through the size of micro- areas that integrates georeferenced location and historical monthly energy consumption. The third and last stage correlates the maps obtained in ArcGIS, over positioning them, in such a way to have the optimal locations of the solar parks, considering all variables and conditions; for the long term horizon period (2030), which will be connected near the Medium Voltage (M.V.) electrical networks to determine the optimal location of the solar parks in the whole area of EEASA's concession. The voltage drop study was performed in the CYME software, CYMDIST package, from which the load flow simulation (unbalanced method) was developed, resulting in the M.V. network, integrated by its respective feeders, does not exceed to a disproportionate extent the allowed range limit of 6% established by the ARCERNNR 002-20 regulation, to implement future renewable energy generations.